An Interactive Design System for Hybrid ICs. (1981) - Shiraishi, Hiroshi; Kawamura, Kaoru; Hayashi, Masaaki
Abstract : In hybrid integrated circuit mask design, the design quality largely depends on the designer's experience and creativity. It is difficult to completely automate the design process as is done with LSIs or printed circuit boards. It is important to incorporate flexibility into the system. This paper describes an interactive design system for laying out hybrid ICs. The system is implemented on a large host computer, and graphic display terminals are connected to it in a time sharing environment. The system provides designers with many interactive facilities which are useful in designing hybrid ICs. In addition to highly interactive dialogue, the system has capabilities such as dynamic checking of the designer's operations against a set of design rules, or automatic generation of standardized element patterns. The system outputs mask information, design documents and so on which are used in the CAM of hybrid ICs. The system is being used at Fujitsu and is contributing to high reliability of the design, and shortening the design period.